The role of surgical management in primary small bowel lymphoma: A single-center experience. Issue 10 (October 2017) - Hong, Y.-W.; Kuo, I.-M.; Liu, Y.-Y.; Yeh, T.-S.
Abstract: Introduction: Information on primary small intestinal lymphoma is more limited than for gastric lymphoma because most of the previous studies did not focus on the former. Few prognostic indicators in primary intestinal lymphoma have been reliably established because of limited patient numbers and variations in criteria for patient selection. In this study, we retrospectively reviewed the clinical and pathological characteristics of small intestinal lymphoma cases from our hospital, to determine prognostic factors and to clarify the effect of surgical resection on prognosis. Methods: Eighty-two patients were enrolled in this retrospective study between January 1997 and December 2012. Patients were divided into two groups based on whether or not they underwent surgical management. Gross resection was defined as complete removal of the primary lesion(s), as confirmed by the naked eye. Combined therapy refers to concurrent surgery and chemotherapy. The clinicopathological characteristics and long-term outcomes of patients were analyzed and compared between the two groups. Results: Most of the patients had abdominal pain (75.6%), and some had loss of body weight (29.3%) and bowel perforation (22.0%). Sixty-two patients (75.6%) underwent surgical management. Patients in the surgery group presented with fewer B symptoms (fever, night sweats, and weight loss; P  = 0.035) but more bulky disease ( P  = 0.009). The ileocecal region was the most common site of solitary involvement (34.1%). The most common reason for surgery was for tumor-related complications (61.3%). Seven patients (11.3%) developed major complications of surgery, but these were not related to the indication, timing, or type of surgery. Only major surgical complications were statistically significant in relation to early mortality ( P  = 0.004). The estimated 5-year progression-free survival (PFS) was 35.1% and 5-year overall survival (OS) was 43.2%. Univariate analysis revealed that patients in the surgery group had improved 5-year PFS ( P  = 0.028). T-cell lymphoma, involvement of multiple gastrointestinal regions and extranodal involvement, higher scores for International Prognostic Index (IPI), more advanced Ann Arbor stage, lactate dehydrogenase (LDH) levels above 215 U/L, and management without combined therapy were prognostic for shorter PFS and OS in univariate analyses. Individuals who received R0 resection or gross resection had improved 5-year PFS and OS. Cox regression analysis demonstrated that primary T-cell lymphoma was an independent negative prognostic factor for both OS and PFS. Conclusion: Combined therapy is an independent prognostic factor for long-term survival in small intestinal lymphoma. Gross resection is recommended in patients with small intestinal lymphoma and leads to improved PFS without significantly increasing the risk of complications. Emergency surgery does not lead to poor prognosis. However, caution is warranted in the management of all patients, because of the high risk of post-operative complications and potential for early mortality.